Analisis faktor dalam pengambilan keputusan wisatawan pada wisata Pulau Pari Gugusan Pulau Seribu - Maesari, Siti; Irwansyah , Novi; Sutomo; Fermica Iskandar, Merrisa (Universitas Tangerang Raya, 2024)
This research aims to analyze the factors that tourists consider when making decisions to travel to Pari Island in the Thousand Islands group. This research uses primary data with a quantitative approach and a research instrument in the form of a questionnaire which was distributed to 100 respondents using a simple random sampling technique. Instrument testing in this research uses validity and reliability tests, data analysis techniques use descriptive analysis and factor analysis. The number of variables studied was 6 data variables processed using SPSS 26 For Windows. The results of the research show that from the 6 variables analyzed using the factor analysis model a new factor was created, namely the tourist destination factor with an eigin value of 3.479, the cumulative percentage of variance of the extracted factors was 57.980%, which means that the results of the research formed were able to explain the factors that resulted. The decision of tourists to travel to Pari Island in the Thousand Islands group was 57.980%.